Comparative evaluation of conventional and socket-shield techniques on maxillary esthetics following immediate implant placement in fresh extraction sockets: A randomized controlled trial - Farhan Durrani; Aishwarya Pandey; Shweta Ahlawat; Ekta Kumari; S. U. Gokila Vani; Sakshi Agarwal; P. G. Naveen Kumar (Journal of Indian Society of Periodontology)
Background: Dental implants in fresh extraction sockets of the maxillary esthetic area are technique-sensitive procedures where retaining a buccal root segment can enhance periodontium preservation and esthetics. This study aims to compare marginal bone levels and esthetic outcomes between conventional immediate implant placement and the socket-shield technique in fresh maxillary extraction sockets. Materials and Methods: Twenty-four patients with type 1 extraction sockets were included in this randomized trial and assigned to either conventional immediate implant placement or the socket-shield technique. Implant survival, crestal bone levels, and pink esthetic scores (PES) were evaluated at 8 months (temporary prosthesis), 12 months, and 36 months (final crowns). Results: All implant-supported restorations were successful within the study’s observation period. The socket-shield technique showed significantly lower marginal bone loss (e.g. 1.40 ± 0.29 mm vs. 1.70 ± 0.36 mm at 36 months; P = 0.040) and superior PES (e.g., 10.50 ± 0.90 vs. 9.36 ± 0.98 at 36 months; P = 0.008) compared to the conventional technique. However, the technique’s complexity underscores the need for expertise and careful execution to optimize tissue preservation in the maxillary esthetic zone. Conclusion: The socket-shield technique better preserves hard and soft tissues around implant-retained prostheses than conventional implant placement in maxillary esthetic regions. Further studies with larger sample sizes and longer follow-up are required to validate these findings.